Design and modeling of a photoacoustic gas analyzer with a thermal source for carbon isotope ratio analysis; Atmospheric and Oceanic Optics; Vol. 28, iss. 5 - Osipov K. Yu. Konstantin Yuryevich; Kapitanov V. A. Venedikt Andreevich; Ponomarev Yu. N.; Karapuzikov A. I . (2015, 2015)
Title screen